Without My Family, I Don't Know If I Would Be Here: The Role of Families in Supporting Latinx Computer Science Students at HSIs - Jessica Rivera; Anne-Marie Núñez; Igdalia Covarrubias (MDPI AG, 2024)
The underrepresentation of diverse communities in STEM disciplines, particularly in computer science, remains a significant challenge. This study investigates the experiences of Latinx students at Hispanic-Serving Institutions (HSIs) within computer science departments that are actively working to increase Latinx graduation rates. Utilizing data from ethnographic case studies, we conduct a thematic analysis through the lenses of Yosso's community cultural wealth model and Rendón's validation model to examine the pivotal role families play in fostering the success of Latinx students in computer science at HSIs. Our findings reveal that families provide essential encouragement, serve as a source of motivation to combat isolation, and celebrate students' achievements in their pursuit of computer science careers. Recognizing the critical contributions of familial support is essential for enhancing the success of Latinx students in one of the most underrepresented fields within STEM. These insights are crucial for developing strategies that can effectively promote diversity and inclusion in computer science.